Empowering recovery: a remote spirometry system and mobile app for monitoring and promoting pulmonary rehabilitation in patients with rib fracture - Ling-wei Kuo; Chih-Yuan Fu; Chien-An Liao; Chien-Hung Liao; Chi-Tung Cheng; Tai-Horng Young; Shih-Ching Kang; Szu-An Chen; Yu-San Tee (Trauma Surgery & Acute Care Open)
Background Multiple rib fractures commonly result from blunt chest trauma. These fractures can lead to prolonged impairment in pulmonary function and often require long-term rehabilitation. This pilot study aimed to evaluate the feasibility of a remote spirometry device for continuous monitoring of lung function in patients with multiple rib fractures.Methods Between January 2021 and April 2021, we implemented a remote spirometry system for adult patients with multiple rib fractures and collected their clinical data. We used a Restart system to monitor the respiratory parameters of patients. This system included a wireless spirometer and a Healthy Lung mobile application. A portable spirometer was used to measure forced vital capacity (FVC), peak expiratory flow (PEF), and forced expiratory volume in 1 second.Result In total, 21 patients were included in this study. We categorized the participants into two age groups: those older and those younger than 65 years. No significant differences were observed between the two groups regarding demographic characteristics or device adoption rates. However, we observed that patients under 65 years demonstrated more remarkable improvement in pulmonary function than their older counterparts, with significant differences in FVC (110% vs 10%, p=0.032) and PEF (64.2% vs 11.9%, p=0.003).Conclusion The adoption of the remote spirometry device is similar between older and younger patients with rib fractures. However, the device improves pulmonary function more in patients in a younger age group. This tool may be effective as a real-time, continuous pulmonary function monitoring system for patients with multiple rib fractures.Level of evidence Level IV.